Malaysian tertiary level ESL students’ perceptions toward teacher feedback, peer feedback and self-assessment in their writing - Vasu, Kayatri; Ling, Chai Hui; Nimehchisalem, Vahid (Australian International Academic Centre, 2016)
In Malaysia, teacher feedback is highly preferred by students, who often believe that teachers know best. Teacher feedback shows them their teacher’s idea of an ideal writing. However, excessive dependence on teachers adds to their workload. Therefore, teachers are increasingly promoting two other alternative methods that are gradually gaining importance. These methods are peer feedback and self-assessment. This study investigates ESL students’ perceptions toward teacher feedback, peer feedback and self-assessment in students’ writing process. Questionnaires, adapted from the instruments in the literature, were administered to 107 randomly selected students in a private local university in Malaysia. Students found feedback given to the content and organization of their writing more useful than feedback provided for their vocabulary and grammar. It was also found that students perceived feedback from teacher, peers and self-assessment all as highly useful. Additionally the results indicated while there was no significant difference (p > .05) between the students’ perceptions toward teacher feedback and self-assessment, they were both perceived as significantly more useful (p < .001) than peer feedback. The students also perceived explicit feedback as significantly more useful (p < .001) than implicit feedback. The results of this study have implications for English language learning-teaching practitioners and researchers. They shed light on the options preferred by students in revising their writing in ESL writing classrooms. Future research on the effects of teacher feedback, peer feedback and self-assessment on students’ writing performance will provide better insight on the preferred methods in ESL writing classrooms in similar settings.